Identification and lipolytic activity of Bacillus and Staphylococcus strains from shrimp paste (Ka-pi) - Rungsima Daroonpunt, Patcharin Saeng-in, Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2019)
Twelve bacterial strains were isolated from shrimp paste (Ka-pi) by the standard dilution technique using nutrient broth (NB) medium supplemented with 5% NaCl (w/v). Six rod-shaped isolates were belonged to the genus Bacillus and six coccal isolates were belonged to the genus Staphylococcus based on their phenotypic characteristics and 16S rRNA gene sequence analyses (98.91%–100% sequence similarity). Strain KP1-09 was identified as Bacillus tequilensis, KP1-04 and KP2-03 as B. infantis, KP1-14 as B. flexus, KP2-17 as B. paramycoides, and KP1-10 as Bacillus species. Coccal isolates, KP3-03, KP4-02, KP4-08, KP5-02, KP5-03, and KP5-07 were identified as Staphylococcus cohnii subsp. urealyticus. The lipase activity of strains in modified NB and in modified NB medium supplemented with 1% (v/v) Tween 20 or Tween 80 using para-nitrophenyl butyrate (C4) as a substrate ranged from 4.41 ± 0.17 Unit/ ml to 29.68 ± 0.80 Unit/ml. The strain B. flexus KP1-14 cultivated in modified NB medium showed the highest lipase activity, while the strains KP1-10, KP1-09, KP4-02, KP5-02, and KP5-07 cultivated in modified NB medium supplemented with 1% (v/v) Tween 80 showed the lipase activity ranged from 0.32 ± 0.01 Unit/ml to 3.22 ± 0.24 Unit/ ml when p-nitrophenyl palmitate (C16) was used as a substrate. The strain S. cohnii subsp. urealyticus KP5-02 showed the highest lipase activity.
Keywords: Bacillus, lipase, 16S rRNA gene sequence, shrimp paste, Staphylococcus.